الدلالات الفقهية والمقاصدية في الأحاديث النبوية التي تعزز الأوامر والتوجيهات الوقائية تجاه جائحة كورونا: دراسة تطبيقية تحليلية - العضياني، النيرة بنت بدر بن غزاي (جامعة أم القرى, 2020)
The importance of my research is that it deals with the descending of the most prominent catastrophes of the modern era at the collective, societal and global levels, where the actions of governments and the directives of the role of Fatwa in the world related to the lives of individuals, groups, governmental and private institutions, so I imposed stone and isolation, and disrupted rituals and collective worship... so I had to address these The pandemic from a jurist’s point of view is my purpose, so I chose the prophetic hadiths that have the orbit of dependence on graduating the jurisprudential rulings related to Corona from acts of worship and the like, and I extracted the juristic indications from these hadiths and applied them to this descending, through explanations of hadiths and books of Islamic jurisprudence, by mentioning the face of inference and witnessing it, I also extracted the intentional connotations from these hadiths, Through the Books of Purposes and Origins, it was concluded with a conclusion that included the most prominent results and the summary of the research, the most prominent of which are: the need for collective spacing, the need for quarantine on the injured, the need to obey the rulers and scholars by disrupting the gathering and groups and the Hajj and Umrah due to the coronary epidemic of self preservation, and the prevention of the spoils and risks of the epidemic, with Recommendation to establish a data bank that includes jurisprudence and Maqasid rules concerning the events and emerging reality.
تتمثل أهمية بحثي هذا كونه يعالج نازلة من أبرز نوازل العصر الحديث على المستوى الجماعي، والمجتمعي، والعالمي، حيث تعلقت إجراءات الحكومات، وتوجيهات دور الإفتاء بحياة الأفراد، والجماعات، والمؤسسات الحكومية والخاصة، ففرضت الحجر، والعزلة، وأوقفت الشعائر، والعبادات الجماعية... فكان لزاما أن أتناول هذه الجائحة من منظور فقهي مقاصدي حديثي، فقمت باختيار الأحاديث النبوية التي عليها مدار الاعتماد في تخريج الأحكام الفقهية المتعلقة بكورونا من عبادات، ومعاملات، ونحوها، واستخرجت الدلالات الفقهية من هذه الأحاديث وتطبيقها على هذه النازلة، من خلال شروح الأحاديث، وكتب الفقه الإسلامي، بذكر وجه الاستدلال وشاهده، كما قمت باستخلاص الدلالات المقاصدية من تلك الأحاديث النبوية من خلال كتب المقاصد، والأصول، وختمت بخاتمة تضمنت أبرز النتائج، وخلاصة البحث، وأبرزها: لزوم التباعد الجماعي، ولزوم الحجر الصحي على المصاب، ولزوم طاعة ولاة الأمر، والعلماء بتوقيف الجمع، والجماعات، والحج، والعمرة بسبب وباء كورونا لحفظ النفس، ودرء المفاسد، والمخاطر المترتبة على الوباء، مع توصية بإنشاء بنك معلوماتي يتضمن القواعد الفقهية والمقاصدية التي تخص النوازل، والواقعات المستجدة.
Keywords: الفقه الإسلامي -- الأحاديث النبوية -- جائحة كورونا -- مقاصد الشريعة -- حفظ النفس